Chemokines in the Pathogenesis and as Therapeutical Markers and Targets of HCV Chronic Infection and HCV Extrahepatic Manifestations - Fallahi, Poupak; Martina Ferrari, Silvia; Giuggioli, Dilia; Sebastiani, Marco; Colaci, Michele; Ferri, Clodoveo; Antonelli, Alessandro (Current Drug Targets, 2017)
Cytokines and chemokines, hepatitis C virus (HCV) infection-induced, participate in viral control and liver damage. The complex cytokine network, operating during initial infection allows a coordinated and effective development of innate and adaptive immune responses. “HCV interferes with cytokines at various levels and escapes immune response by inducing a T helper (Th)2/T cytotoxic 2 cytokine profile”. A predominance of the Th1 immune response (and related cytokines) has been evidenced in chronic hepatitis C infection and in extrahepatic manifestations. Interferon (IFN)-γ and IFN-γ-inducible chemokine (C-X-C motif) ligand (CXCL)9, -10 and -11 recruit inflammatory infiltrates into the liver parenchyma due to the incapability to control the infection process, resulting in extensive liver damage and liver cirrhosis. “The most important systemic HCV-related extrahepatic diseases — mixed cryoglobulinemia, lymphoproliferative disorders, diabetes and autoimmune thyroid disorders — are associated with a complex dysregulation of the cytokine/chemokine network and involve pro-inflammatory and Th1 chemokines. The therapeutical administration of cytokines such as IFN-α may result in viral clearance during persistent infection and reverts this process” reducing circulating CXCL10 levels. “Several studies have reported interleukin (IL)-28B polymorphisms, and circulating CXCL10, may be prognostic markers for HCV treatment efficacy in HCV infection”. Other studies have also shown that HCV clearance by directly acting antiviral agents therapy decreases circulating CXCL10 levels. “Theoretically agents that selectively neutralize CXCL10 could increase patient responsiveness to traditional IFN-based HCV therapy”, simultaneously reducing inflammatory immune cell activation.
Keywords: IFN inducible chemokines